Optimization of the production of capsules with microstakes to increase the storage time of the Mexican medicinal plant Castilleja tenuiflora (Orobanchaceae) - León Romero, Yatzil; Trejo Espino, José Luis; Salcedo-Morales, Guadalupe; Trejo-Tapia, Gabriela; Evangelista Lozano, Silvia (Instituto de Ecología, A.C., 2019)
Background and Aims: Castilleja tenuiflora is one of the Mexican, wild and medicinal plants cultivated in vitro which have anti-inflammatory and antiulcerogenic biological activity. The encapsulation of microstakes is an option to propagate and prolong the storage of this plant. Therefore, the objective of this study was to establish a method for the encapsulation and conservation of C. tenuiflora microstakes that does not affect the content of the compounds of interest of this plant.Methods: Capsules were elaborated with sodium alginate in complex with calcium chloride dihydrate as matrix and tissue microstakes from seedlings grown in vitro. Different concentrations and polymerization times were tested, as well as different storage times and temperature, for later analysis of the major metabolites of the methanolic extracts by chromatography (HPLC) of the resulting plants.Key results: The combination for the production of capsules with microstakes is 3% sodium alginate and calcium chloride dihydrate at 50 mM, with 25 minutes of polymerization. The seedlings derived from synthetic seeds and stored for 100 days presented the same compounds as the donor plants.Conclusions: The encapsulation of C. tenuiflora microstakes with sodium alginate and calcium chloride dihydrate allows the storage of plant material and the main compounds are maintained. Hence, this method for the encapsulation and conservation of microstakes is an alternative to maintain the genotype of elite plants and counteract the illegal collection of wild plants.